Number of Machine and Material Requirements for Production Planning of Tablet Tooling with the Demand of 200 Units/Day - Nanang Qosim; Andre Kurniawan; Moh. Nasir Hariyanto; Zakki F. Emzain; Moh. Hartono; AM Mufarrih (Journal of Applied Engineering and Technological Science (JAETS), 2021)
Shaping and marketing a product in tablet form is an easy and economical alternative to product shaping. Products in tablet form now cover almost all fields, so that the demand for tablet tooling of various sizes and variations continues to increase. As an effort to support the effectiveness and proper industrial planning, it is necessary to carry out an analysis of the machine and material requirements to produce tablet tooling which is the aim of this study. To achieve these objectives, the methods used in this study include product design, operation plan analysis, and calculation of material requirements and number of machines. The result shows that the number of machine requirements to manufacture the die and punch of tablet tooling with the demand of 200 unit/day are two units of power hacksaw, five units of lathe machine, and a unit of milling machine. On the other hand, the material requirements needed in one day are 22.24 m (Ø45 mm x 5 bars) and 12.79 m (Ø18 mm x 3 bars).